Effectiveness and safety of rhIGF1 therapy in patients with or without Laron syndrome. Issue 2 (February 2021) - Bang, Peter; Woelfle, Joachim; Perrot, Valerie; Sert, Caroline; Polak, Michel; ,
Abstract : Objective: The European Increlex ® Growth Forum Database Registry monitors the effectiveness and safety of recombinant human insulin-like growth factor-1 (rhIGF1; mecasermin, Increlex ® ) therapy in patients with severe primary IGF1 deficiency (SPIGFD). We present data from patients with and without a reported genetic diagnosis of Laron syndrome (LS). Design: Ongoing, open-label, observational registry (NCT00903110). Methods: Children and adolescents receiving rhIGF1 therapy from 10 European countries were enrolled in 2008–2017 ( n = 242). The treatment-naïve/prepubertal (NPP) cohort ( n = 138) was divided into subgroups based on reported genetic diagnosis of LS ( n = 21) or non-LS ( n = 117). Multivariate analysis of the NPP-non-LS subgroup was conducted to identify factors predictive of growth response (first-year-height standard deviation score (SDS) gain ≥ 0.3). Assessments included change in height and weight over 5 years and adverse events (AEs). Results: Height SDS gain from baseline was greater in the NPP-LS than the NPP-non-LS subgroup after 1 years' treatment ( P < 0.05). In the NPP-non-LS subgroup, 56% were responders; young age at baseline was a positive independent predictive factor ( P < 0.001). NPP-non-LS-responders and the NPP-LS subgroup had a similar mean age (6.07 years vs 7.00 years) at baseline and height SDS gain in year 1 (0.64 vs 0.70), although NPP-non-LS-responders were taller ( P < 0.001) at baseline. BMI SDS changes did not differ across subgroups. Treatment-emergent AEs were experienced by 65.3% of patients; hypoglycaemia was most common. Conclusions: In most NPP children with SPIGFD, with or without LS, rhIGF1 therapy promotes linear growth. The safety profile was consistent with previous studies.